Corrosion protection performance of silicon-based coatings on carbon steel in NaCl solution: a theoretical and experimental assessment of the effect of plasma-enhanced chemical vapor deposition pretreatment. Issue 24 (25th May 2022) - Delimi, Amel; Ferkous, Hana; Alam, Manawwer; Djellali, Souad; Sedik, Amel; Abdesalem, Kahlouche; Boulechfar, Chérifa; Belakhdar, Amina; Yadav, Krishna Kumar; Cabral-Pinto, Marina M. S.; Jeon, Byong-Hun; Benguerba, Yacine
Abstract : Using a plasma-assisted chemical vapor deposition (PACVD) process, carbon steel samples were coated with an organosilicon layer less than 2.5 microns thick. Abstract : Using a plasma-assisted chemical vapor deposition (PACVD) process, carbon steel samples were coated with an organosilicon layer less than 2.5 microns thick. Ellipsometry, Fourier transform infrared (FTIR) spectroscopy, contact angle, scanning electron microscopy (SEM), and atomic force microscopy (AFM) were used to analyze the films. Additionally, gravimetric experiments were used to determine the electrochemical properties of the organosilicon coatings. Organosilicon-coated carbon steel specimens demonstrated significantly enhanced resistance to corrosive conditions, such as 3% aqueous sodium chloride solutions. The surface preparation method has a considerable influence on the morphological and electrochemical properties of the steel. Argon pretreatment significantly enhances the corrosion resistance of organosilicon-coated steel. Gravimetric research demonstrated that pretreatment with argon plasma resulted in less weight loss and corrosion than pretreatment with nitrogen plasma. The link between quantum computing and experimental data using density functional theory (DFT) and molecular dynamics (MD) was used.